PASRAMAN PARENTAS AND INTERNALIZATION OF HINDU-KAHARINGAN MORAL VALUES AMONG STUDENTS IN PALANGKA RAYA CITY - Agung Adi; Dewi Sinta (UHN I Gusti Bagus Sugriwa Denpasar, 2025)
This study analyzes the internalization of character education based on Hindu and Kaharingan values at Pasraman Parentas, focusing on customs, ritual experiences, and teacher role models. Data were collected through participatory observation, semi-structured interviews, and document analysis, then analyzed thematically. The findings reveal three pillars of character building: Hindu ethical education (tat twam asi and telu kapatut), reinforcement of values through rituals (Basarah, Tri Sandhya, Yoga), and teachers as role models. Character education here is not limited to cognition, but integrates cognition, emotion, and action. Habituation through social interaction, active participation in rituals, and teachers who serve as role models effectively foster honesty, self-control, loyalty, discipline, responsibility, and awareness of unity. This holistic and contextual model, which combines Hindu teachings and local Kaharingan wisdom, has proven effective in shaping students' moral and spiritual identities while remaining relevant in the context of multiculturalism and the challenges of globalization.